DETECTION OF DEADLOCKS IN PARALLEL PROGRAMS AS SOLUTION OF LINEAR DIOPHANTINE EQUATIONS - Olga F. Babakhyan (Вестник Донского государственного технического университета, 2018)
The method of detecting deadlocks in the distributed systems at the design stage of the system is considered. The system is presented in the form of a model through the formal specification by means of Petri nets.